A Comparative Analysis of the European U-Space Framework and the US-American UAS Traffic Management (UTM) System - Lieb, Teemu Joonas; Sievers, Tim Felix (IEEE/AIAA Digital Avionics Systems Conference, 2024)
In recent years, Uncrewed Aircraft Systems (UAS), commonly known as drones, have emerged as pivotal tools facilitating innovative business models and diverse applications across industries and nations. In Europe, the introduction of the U-space concept through the Warsaw Declaration in 2016 marked a key step towards integrating drones into the existing airspace. In 2021, the European Commission introduced specific regulations, which established a regulatory framework for the U-space ecosystem. In the United States (US), a parallel initiative known as the UAS Traffic Management (UTM) system aims to seamlessly integrate drones into low-altitude airspace, focusing, among other, on BVLOS operations. An initial conceptual framework for UTM was first conceived by the National Aeronautics and Space Administration (NASA) in 2013. In 2023, the US Federal Aviation Administration (FAA) released the UTM Implementation Plan as mandated by Congress in the FAA Reauthorization Act of 2018. This paper provides a comparative analysis of these two frameworks, with particular emphasis on newly implemented aspects such as concepts for dynamic airspace management, electronic conspicuity, emerging new flight rules and flight authorization processes. Key aspects examined in this paper include system architecture principles, relevant stakeholders, envisaged digital services and required procedures for UAS operations. This paper aims to provide valuable insights into the evolving landscape of drone integration within airspace management frameworks, shedding light on the synergies and disparities between European and US approaches.